Surface Behavior and Lipid Interaction of Alzheimer β-Amyloid Peptide 1–42: A Membrane-Disrupting Peptide - Ambroggio, Ernesto E. (Biophysical Society, 2005)
Amyloid aggregates, found in patients that suffer from Alzheimer's disease, are composed of fibril-forming peptides in a β-sheet conformation. One of the most abundant components in amyloid aggregates is the β-amyloid peptide 1–42 (Aβ 1–42). Membrane alterations may proceed to cell death by either an oxidative stress mechanism, caused by the peptide and synergized by transition metal ions, or through formation of ion channels by peptide interfacial self-aggregation. Here we demonstrate that Langmuir films of Aβ 1–42, either in pure form or mixed with lipids, develop stable monomolecular arrays with a high surface stability. By using micropipette aspiration technique and confocal microscopy we show that Aβ 1–42 induces a strong membrane destabilization in giant unilamellar vesicles composed of palmitoyloleoyl-phosphatidylcholine, sphingomyelin, and cholesterol, lowering the critical tension of vesicle rupture. Additionally, Aβ 1–42 triggers the induction of a sequential leakage of low- and high-molecular-weight markers trapped inside the giant unilamellar vesicles, but preserving the vesicle shape. Consequently, the Aβ 1–42 sequence confers particular molecular properties to the peptide that, in turn, influence supramolecular properties associated to membranes that may result in toxicity, including: 1), an ability of the peptide to strongly associate with the membrane; 2), a reduction of lateral membrane cohesive forces; and 3), a capacity to break the transbilayer gradient and puncture sealed vesicles.